2000
DOI: 10.1002/etc.5620190520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4‐nonylphenol on fecundity and biomarkers of estrogenicity in fathead minnows (Pimephales promelas)

Abstract: Abstract-Adult fathead minnows (Pimophales promelas) were exposed to waterborne concentrations of 4-nonylphenol (NP) ranging from 0.05 to 3.4 g NP/L for 42 d. Results were similar, but slightly different, for two experiments conducted during July and August, near the beginning of the breeding season, and a second experiment conducted during September and October, at the end of the breeding season, during which the adults were maintained continuously in breeding condition. Inverted U-type doseresponse relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…The GVBD inhibition was attributed to the estrogen agonistic action of 4-NP. The estrogenic property of 4-NP was also shown by Baek, Park, Lee & Kim (2003) in longchin goby Chasmichthys dolichognathus and by Giesy et al (2000) in fathead minnow Pimephales promelas.In catfish, low concentrations of 4-NP up to 10 ng/mL stimulated GVBD and the higher concentrations inhibited it. The species variation may be one factor for different responses to 4-NP in the GVBD assay.…”
Section: Discussionmentioning
confidence: 81%
“…The GVBD inhibition was attributed to the estrogen agonistic action of 4-NP. The estrogenic property of 4-NP was also shown by Baek, Park, Lee & Kim (2003) in longchin goby Chasmichthys dolichognathus and by Giesy et al (2000) in fathead minnow Pimephales promelas.In catfish, low concentrations of 4-NP up to 10 ng/mL stimulated GVBD and the higher concentrations inhibited it. The species variation may be one factor for different responses to 4-NP in the GVBD assay.…”
Section: Discussionmentioning
confidence: 81%
“…Asterisks show significant differences from controls (PB0.05). minnow, Pimephales promelas, a freshwater multiplespawning species, NP increased the plasma E2 levels and decreased egg production, although NP decreased plasma vitellogenin levels at the beginning of the breeding season (Giesy et al 2000). The induction of vitellogenin is reported to be one of the most sensitive biomarkers for assessing estrogenic effects (Heppell et al 1995;Sumpter and Jobling 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of vitellogenin is reported to be one of the most sensitive biomarkers for assessing estrogenic effects (Heppell et al 1995;Sumpter and Jobling 1995). However, Giesy et al (2000) reported that the vitellogenin assay is inappropriate for multiple-spawning species such as the fathead minnow because plasma E2 levels remain high during the spawning period. In addition, they concluded that NP increased endogenous E2 levels and then inhibited egg production via an indirect mechanism and not a direct estrogen-agonistic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Vitellogenin protein levels often increase in fish exposed to pulp and paper mill effluents [7] due to the activation of ERa by estrogen or estrogenic compounds or by androgenic substances that may be metabolized to have estrogenic effects [28,29]. Elevated VTG mRNA levels have been observed in juvenile whitefish (Coregonus lavaretus) caged downstream from bleached kraft mills [11].…”
Section: Expression Analysis Suggests That Effluents Contained Edcsmentioning
confidence: 99%